Norman Fairclough's Critical Discourse Analysis in Deddy Corbuzier's Podcast Title“PEMERINTAHNYA MANA NIH⁉ ???? SI KAKEK PENYELAMAT FYP INDONESIA‼ MBAH GURUMATEMATIKA” on YouTube - Ulfa Kurniasari; Dyah Ayu Kusuma; Irma Khoirot Daulay; Toyyibah Toyyibah (Journal of Pedagogi, 2024)
This research aims to analyze one of Deddy Corbuzier's podcast titles on YouTube using Norman Fairclough's Critical Discourse Analysis (CDA) approach. Analysis was carried out on three dimensions of CDA, namely text, discourse practice, and social practice. This research uses a qualitative descriptive method with the CDA Fairclough approach. The CDA approach allows for in-depth analysis of how podcast titles reflect and shape ideology, power, and identity. The research results show that the podcast title contains complex discourse content and is related to relations of power and domination in society. The findings reveal that the title reflects societal discontent with governmental performance and advocates for new leadership capable of fostering positive change. Fairclough's CDA illuminates how the title constructs and reinforces power relations within Indonesian society, employing provocative language to incite debate and engage viewers emotionally. This analysis underscores the role of media in shaping   DOI: public discourse and influencing perceptions. By critically evaluating media content, this study contributes to understanding how language and discourse strategies can shape ideological perspectives and societal expectations. Ultimately, the podcast title serves not only as a critique of current governance but also as a catalyst for broader discussions on leadership and societal transformation in contemporary Indonesia.